Structural Aspect of Checking the Continuity of the Enterprise during Internal Audit - Selishchev, S. V. (Statistics of Ukraine, 2020)
The article presents the results of the study and the further development of approaches to assessing the continuity risks associated with the internal audit of the enterprise. Particular attention is given in the article to the organization of internal audit of termination of activity for groups of events or conditions, which alone or in the aggregate may call into question the validity of the assumption of continuity of activity. The purpose of the article is to research and further develop approaches to assessing the risk assessment of the impact of internal audit effectiveness on the auditor’s assessment of the risk of termination of the enterprise. Current practice research shows that the implementation of an element of internal control, such as internal audit, is either not used at all, or is carried out in a purely formal manner. In particular, it concerns the control over the financial statements, which indicate the probability of termination of the enterprise. In turn, the lack or low efficiency of the internal audit service, whose main task is to monitor the internal control system, causes an increase in audit risk of control, which in turn increases the overall level of audit risk. This situation necessitates an increase in volumes and as a result of audit time. In view of the results of the conducted researches of the current practice of functioning of the internal audit service at the enterprises, in most cases there is a purely formal approach to its functions, in particular in the aspect of ensuring control over the financial status indicators, the critical values of which can directly lead to the termination of the activity of the enterprise. The analysis of the scientific and methodological base shows the lack of materials, the organization of an effective system of internal control over strategic financial indicators, and as a consequence of the lack of an effective concept of its monitoring by the internal audit. We have proposed a comprehensive functional model that includes the following elements: 1) setting an assignment for the internal audit service; 2) identification of sources of necessary information and method of assessment of its reliability; 3) conceptual basis for ensuring the performance of internal audit functions.